Legal Education as an Effort to Improve the Quality of Knowledge through Family Welfare Empowerment (PKK) in Nongkosawit Village - Zain Arfin Utama; Pandam Bayu Seto Aji; Muhamad Chabib F; Qolbi Hanif Fadhlulloh; Eko Setiyo Ary Wibowo (Sustainable Society Journal, 2026)
Legal education is a strategic effort to increase public awareness of legal rights and obligations, particularly in the context of preventing sexual violence and protecting women and children. Nongkosawit Village, Semarang, is one of the areas requiring legal education intervention due to the high rate of gender-based violence and the community's lack of understanding of reporting and law enforcement mechanisms. This study aims to evaluate the effectiveness of legal education conducted in collaboration with the Family Welfare Development (PKK) in increasing public understanding of the law, particularly regarding Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Government Regulation Number 45 of 2007 concerning Child Protection. The methods used included legal counseling, group discussions, training, legal exhibitions, and the use of social media. The results show a significant increase in public understanding of legal rights and obligations, as well as increased PKK participation in violence prevention efforts. This legal education also has an impact on improving the community's quality of life through the development of legal skills and awareness. The conclusion of this study emphasizes the importance of collaboration between educational institutions, local governments, and community organizations such as the PKK in implementing sustainable legal education programs.